ANALISIS STILISTIKA DAN NILAI PENDIDIKAN KARAKTER DALAM LIRIK-LIRIK LAGU FOURTWNTY ALBUM LELAKU SERTA RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA INDONESIA TINGKAT SMA - Arina Dicka Maretta; Elisabeth Nugraheni Eko Wardani; Atikah Anindyarini (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This is descriptive qualitative research using stylistic analysis to describe the existence of language style, diction, image, educational values of the character, and the relevance of the lyrics of Fourtwnty album Lelaku as a teaching material for Indonesian language learning at high school. Data collection techniques use content analysis and interviews. Validity test of data using medhod triangulation techniques and theory. The results of this study indicate (1) the language style dominated by sinpoke, repetition epizeuksis, and symbolic able to create aesthetic effects, typical, and affirmation; (2) diction is dominated by connotative and typical greetings and names  that can create beauty and uniqueness; (3) the image is dominated by vision capable of generating the image of the reader; (4) the values of character education are dominated by religious values, communicative, hard work, and peaceful love that is expected to shape the character of the reader; and (5) The lyrics of Fourtwnty's album Lelaku can be used and developed as learning materials of class X Indonesian language especially poetry appreciation material on basic competence 3.8 and 4.8.